2021
DOI: 10.1111/jfpp.15317
|View full text |Cite
|
Sign up to set email alerts
|

Stevia polyphenols: A stable antioxidant that presents a synergistic effect with vitamin C

Abstract: Stevia leaves have been claimed to possess the highest antioxidant capacity among botanic foods, yet the antioxidant activity has been attributed to the polyphenols from Stevia leaves (PPS). However, most studies about the PPS were based on Stevia extracts that contain abundant polyphenols and flavonoids. The PPS excluded flavonoids were found to possess antioxidant activity similar to that of epigallocatechin gallate, demonstrating stronger hydrophilic antioxidant activity and stability than that of ascorbic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Due to the diversity of biomass polyphenols, a variety of biological activities has been reported, including antioxidant ( Hu et al, 2020 ; Ji et al, 2020 ), anti-inflammatory ( Myint et al, 2021 ), bacteriostatic ( Martin and Bolling, 2015 ; Gullon et al, 2016 ; Liu et al, 2019 ), anti-tumor ( Sharma et al, 2017 ; Sajadimajd et al, 2020 ), regulation of intestinal flora ( Cardona et al, 2013 ; Suzuki, 2013 ) and prevention of cardiovascular diseases ( Kang, 2013 ; Tangney and Rasmussen, 2013 ; Kitai and Tang, 2017 ; Orr et al, 2020 ). Biomass polyphenols have also been widely used in the fields of the development of drugs and health products.…”
Section: Bioactivity Of Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the diversity of biomass polyphenols, a variety of biological activities has been reported, including antioxidant ( Hu et al, 2020 ; Ji et al, 2020 ), anti-inflammatory ( Myint et al, 2021 ), bacteriostatic ( Martin and Bolling, 2015 ; Gullon et al, 2016 ; Liu et al, 2019 ), anti-tumor ( Sharma et al, 2017 ; Sajadimajd et al, 2020 ), regulation of intestinal flora ( Cardona et al, 2013 ; Suzuki, 2013 ) and prevention of cardiovascular diseases ( Kang, 2013 ; Tangney and Rasmussen, 2013 ; Kitai and Tang, 2017 ; Orr et al, 2020 ). Biomass polyphenols have also been widely used in the fields of the development of drugs and health products.…”
Section: Bioactivity Of Polyphenolsmentioning
confidence: 99%
“… Ji et al (2020) found that the major phenolics in sea buckthorn were flavonoids, phenolic acids, and tannins, which showed antioxidant functions via regulating the activities of cellular enzymes. Myint et al (2021) found that stevia leaves were demonstrated to possess the highest antioxidant capacity among plant foods due to the abundance of polyphenols (PPS). The stevia leaves PPS showed antioxidant activity similar to epigallocatechin gallate (EGCG), and their antioxidant activity, hydrophilic activity, and stability are stronger than ascorbic acid (VC), vitamin E, and chlorogenic acid.…”
Section: Bioactivity Of Polyphenolsmentioning
confidence: 99%
“…AA is sensitive to temperature and is particularly unstable at temperatures above 35°C (Myint et al., 2021). Figure 2d shows the influence of water bath temperature on the absorbance of MoO 3− x nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, as consumers have become conscious about food safety, more interest has been shown in replacing man‐made preservatives with natural preservatives. Antioxidants of bamboo leaves (AOB) and theaflavins (TF) are excellent natural antioxidants that play an important role in inhibiting lipid oxidation and enzyme activity (Xie et al ., 2020; Myint et al ., 2021). Sodium isovitamin (VC) as a common antioxidant has been studied widely (Shang et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%